Three new species of arbuscular mycorrhizal fungi (Glomeromycota) and Acaulospora gedanensis revised - Niezgoda, Piotr; Błaszkowski, Janusz; Błaszkowski, Tomasz; Stanisławczyk, Anna; Zubek, Szymon; Milczarski, Paweł; Malinowski, Ryszard; Meller, Edward; Malicka, Monika; Goto, Bruno Tomio; Uszok, Sylwia; Casieri, Leonardo; et al. (Frontiers in Microbiology, 2024)
Studies of the morphology and the 45S nuc rDNA phylogeny of three potentially undescribed arbuscular mycorrhizal fungi (phylum Glomeromycota) grown in cultures showed that one of these fungi is a new species of the genus Diversispora in the family Diversisporaceae, and the two others are new Scutellospora species in Scutellosporaceae. Diversispora vistulana sp. nov. came from maritime sand dunes of the Vistula Spit in northern Poland, and S. graeca sp.nov. and S. intraundulata sp. nov. originally inhabited the Mediterranean dunes of the Peloponnese Peninsula, Greece. In addition, the morphological description of spores of Acaulospora gedanensis, originally described in 1988, was emended based on newly found specimens and the so far unknown phylogeny of this species was determined. The phylogenetic analyses of 45S sequences placed this species among Acaulospora species with atypical phenotypic and histochemical features of components of two inner germinal walls.